Growth and spectroscopy of new laser crystals Ca₁₀Yb₀.₃K₀.₁(VO₄)₇ - Kosmyna, M.B.; Nazarenko, B.P.; Puzikov, V.M.; Shekhovtsov, A.N.; Yasukevich, A.S.; Kuleshov, N.V.; Gulevich, A.E.; Demesh, M.P.; Gusakova, N.V. (Functional Materials, 2012)
Ca₁₀Yb₀.₃K₀.₁(VO₄)₇ single crystals have been grown for the first time. Absorption and luminescence spectra, luminescence decay kinetics of ²F ₅/₂ level for Yb³⁺ ion are investigated.